A Mixed-Methods Exploration of Women’s Experiences of Anal Intercourse: Meanings Related to Pain and Pleasure - Štulhofer, Aleksandar (Array, 2013)
The aim of this mixed-methods study was to document and analyze the dimensions and meanings of anoreceptive pain and pleasure among heterosexual women. An online survey was carried out on a convenience sample of 1, 893 women aged 18–60 years. Qualitative data were collected using open-ended questions mailed to women who expressed interest in continuing participation in the study ; narratives from 68 women who had experienced anal intercourse were collected and analyzed for pain themes. Most surveyed women had experienced anoreceptive intercourse. A majority of women (79.1 %) reported their first anal intercourse to be painful, but for most of them the intensity and duration of pain/discomfort substantially diminished over time. Less than a third (27.7 %) of participants who regularly engaged in anoreceptive intercourse in the past 12 months stated that they rarely or never experience pain/discomfort with the practice. Nevertheless, most women who continued to practice anal intercourse (58.1 %) reported it to be very arousing and pleasurable. The pleasure associated with anoreceptive intercourse was best predicted by masturbatory frequency and orgasmic ability (with sexual intercourse). The qualitative assessment pointed to a wide range of personal experiences with and meanings attached to pain/discomfort associated with anoreceptive intercourse. Three broad pain themes emerged: (1) pain as insurmountable obstacle, (2) strategic management of pain, and (3) pain eroticization. The study findings suggested that the successful inclusion of anal intercourse into a couple’s sex life is often dependent on a specific learning process.